ANALISA PENGGUNAAN APLIKASI DALAM PENYUSUNAN LAPORAN KEUANGAN PADA UMKM - Bebas Widada, Tri Irawati (Prosiding Seminar Nasional, 2014)
Financial statements is required by all businesses related to the progress and developments that will be assessed by internal and external. In addition, the preparation of the financial statements is the responsibility of the company as an absolute obligation. The preparation of financialstatements require various tools to help easy and sped in the drafting paces. The accounting application that can be used includeMS Excel , MYOB Accounting , Zahir and other programs adapted to the needs of the company.The research used survey method with a questionnaire as adata collection tool to be processed using statistical analysis . The test data using the test data quality (reliability and validity), the classical assumption (normality, multikoliearitas,heterocedastity), , hypothesis testing (multiple linear regression , the coefficient ofdetermination.Based on the results of research by taking a sample of 100 SMEs spread across the city of Surakarta description of the data found 42 % using MS - Excel, 25 % use Accounting Package program and 33 % use the Special Accounting Program. Availability of applications affects the ease of preparation of the financial factor. Availability of applications have influenced the ease of variables, cheap and efficient at 36.40 % while the remaining 63.60 % influenced other variables outside the model .